Amontons-Coulomb-like slip dynamics in acousto-microfluidics - Aurore Quelennec; Jason J. Gorman; Darwin R. Reyes (Nature Communications, 2022)
Acoustic waves can be used to manipulate particles and fluids in biomedical applications. The authors show that slip at the fluid-solid interface, characterized by a lower acoustic transmission into the fluid, is similar to Amontons-Coulomb friction, as found between solids.